Centralized Trading, Transparency, and Interest Rate Swap Market Liquidity: Evidence from the Implementation of the Dodd–Frank Act - Benos, Evangelos; Payne, Richard; Vasios, Michalis (Journal of Financial and Quantitative Analysis, 2020)
We use proprietary transaction data on interest rate swaps to assess the effects of centralized trading, as mandated by Dodd–Frank, on market quality. Contracts with the most extensive centralized trading see liquidity metrics improve by between 12% and 19% relative to those of a control group. This is driven by a clear increase in competition between dealers, particularly in U.S. markets. Additionally, centralized trading has caused interdealer trading in EUR swap markets to migrate from the United States to Europe. This is consistent with swap dealers attempting to avoid being captured by the trade mandate in order to maintain market power.